DIMENSI SOSIAL DALAM TEKS AL-MU’TAZILAH - Eva Farhah (CMES (Center of Middle Eastern Studies), 2020)
Al-Mu'tazilah is a portrait of the Egyptian society which lived at some point in time. As described by Thaha Husain in order to show the disparity in the social life of people who need assistance and attention from the government or the authorities. Although the society lived in modern times at that time, not few other inhabitants still remained in underdeveloped education and social life. Through his work Al-Mu'tazilah, Thaha Husain highlights a range of social dimensions of society. This is the central issue to be addressed in this study. To reveal this social dimension, the sociology of literature theory is used, which focuses on the discussion of the sociology of both the author and the literary works. Primary data relevant to the topic were examined using a qualitative method in order to obtain an objective and scientific analysis. After all course, this study is of interest to the academic community in particular, and to other communities. The benefits are to mimic the social attitudes that can be enforced in today's life. In addition, people may refrain from doing things which might harm the social environment, such as isolating someone from another society.